Ranolazine Reduces Recurrent Ischemia in Patients with Non-ST Elevation ACS - Cunningham, Muriel (MD Conference Express, 2007)
Ranolazine is an anti-ischemic agent indicated for the treatment of chronic angina. Its effects occur without clinically significant changes in heart rate or blood pressure. However, because ranolazine is associated with a mild prolongation of the QTc interval (mean change approximately 6 ms), it currently is indicated only for patients who have not responded to other therapies. Because of this potentially worrisome prolongation of the QT interval, additional safety data were sought.